The Role of the Biy Court Institution in the Formation of the Legal Culture of the Kazakhs - Balabiyev, K.R.; Tursynkulova, D.A.; Kurmanova, A.K. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This paper explores the subject of the traditional institution of Kazakh customary law in the field of justice. The subjects of research are the nature and content of the biy court activities that have been designed to ensure fair and honest consideration and resolution of disputes in the Kazakh steppe. It is especially noted that the activity of the biy court is characterized by the determination of the priority of moral and ethical principles adhered to by the Kazakh society. The scope of activities of this institute determines the relevance of introducing its principles into the modern justice system. The heritage of the biy court is the most important source in the formation and development of the legal culture of the Kazakh society. The paper presents the circumstances of the influence of the biy court on the people of Kazakhstan, not only in matters of consideration and resolution of certain cases and disputes. This refers to the field of political reforms, management issues, on which the institution of biys had social influence based on the knowledge and erudition of the provisions of customary law, the ability to apply them in various situations, and oratorical skills. The paper notes the orientation of the biy court to the moral and ethical principles adhered to in the society. Activities, actions, and decisions taken must be carried out based on humanism, compliance with the committed act and responsibility for it, and punishment. Taking into account the mentality, socio-economic, and political development of the Kazakh society, the national cultural characteristics, as well as the historical experience in resolving various disputes, can be defined as a feature of the biy court that was lost by the modern judicial system.